PENGARUH KUALITAS PELAYANAN, HARGA DAN PROMOSI TERHADAP KEPUASAN PELANGGAN TRANSPORTASI ONLINE GRAB (GRABBIKE) YANG DIGUNAKAN MAHASISWA STIE MAHARDHIKA SURABAYA - Sofyan Lazuardi (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2019)
This research aims to determine the influence of variable quality of service, price and promotion to the satisfaction of the online transport customer Grab both partially and simultaneously. The population in this study is the student of STIE Mahardhika Surabaya regular morning using GrabBike service. The sampling techniques used are purposive sampling as well as the number of samples used amounting to 96 respondents. The type of data used in this study is the primary data by using questionnaires. Data analysis uses multiple linear regression analyses with the help of SPSS 23 programs. After the testing of the hypotheses filed in this study, the value of the variable regression coefficient of service was obtained at 0.207, 0.111, and the promotional variable of 0.323. From Test F obtained a value of F count 119.705 > F table 2.70 as well as significance value 0.000 < 0.05, which means variable quality of service, price and promotion simultaneously affect customer satisfaction. Whereas from a test T variable quality service is obtained the value of t count = 5.356 > T table = 1.986, the variable price is retrieved the value of t count = 2.433 > T table = 1.986 as well as the promotion variable obtained value t count = 6.449 > T table = 1.986, which means a quality variable Services, prices and promotions have a partial effect on customer satisfaction.